Masa Daulah Hamdaniyah: Kemakmuran dan Dinamika Ekonomi di Era Kekuasaan Hamdaniyah - Natasha, Lolitta - (Maliki Interdisciplinary Journal, 2024)
The period of the Hamdanid Daula, which lasted from the 9th to the 10th century AD, was marked by periods of prosperity and economic dynamics in the areas controlled by the Hamdanid dynasty . This abstract will discuss the main aspects of prosperity and economic dynamics that occurred during the Hamdaniyah era. During this time, the Hamdanid dynasty controlled an area that included most of Syria, Lebanon, Iraq and Azerbaijan. They were able to build a stable empire and have an eff ective government. Economic prosperity is achieved through various factors, including strategic geographical location, control over trade routes, and government policies that support economic growth. In the Hamdaniyah era, trade developed rapidly. The Hamdanid rulers built thriving trading cities and stimulated economic growth, such as Aleppo, Mosul and Tripoli. The trade routes connecting the Middle East with the regions of Central Asia, Persia and the Mediterranean Sea became the main source of income for this kingdom. In addition, the agricultural and goods production sectors are also developing rapidly , with plantations, livestock, and manufacturing developing in their areas. Hamdaniyah's power also shows strong economic dynamics. The success of trade and agriculture allowed the accumulation of significant wealth for the ruling families and elites